EFFECT OF SAPPAN WOOD (Caesalpinnia sappan L) EXTRACT ON BLOOD GLUCOSE LEVEL IN WHITE RATS - Saefudin, Saefudin; Pasaribu, Gunawan Trisandi; Sofnie, Sofnie; Basri, Efrida (Indonesian Journal of Forestry Research, 2014)
Sappan wood or kayu secang (Caesalpinia sappan L.) was reported of having medicinal uses, such as for natural antioxidant, relieve vomiting of blood, and ingredients mix for malaria drugs. The research was conducted to study the influence of ethanol extract from sappan wood on blood glucose level of white rats. The blood glucose level in rats was carried out by using glucose tolerance method. It was measured by Reflolux S (Accutrend GC) and Chloropropamide 50 mg/200 g BW (Body Weight) as positive control. The ethanol extracts were used in various concentration 10, 20, 30, 40 and 50 mg/200 g BW per-oral and observed every an hour and beginning one hour before to 7 hours after the extract being administered. The results showed that the administered dose 30 mg/200 g BW of the ethanol extracts equal the positive control. Statistical analysis gave significant differential (P<0,05) in 2 and 3 hour after treatment.